Methods of combating the phenomenon of vibration combustion in low emission combustion chambers of gas turbine installations - Ясиніцький, Е.П.; Левонюк, С.В.; Пустовий, С.О. (Proceedings of National Aviation University (archive), 2009)
The comparative analysis of domestic and foreign experience of vibration burning suppression in low emission combustion chambers of the gas-turbine units is executed, which enabled de bene esse to select two basic groups of methods of vibration burning suppression: passive and active. Basic advantages and failings are shown to each of the selected groups of methods, perspective and high efficiency of the active vibration burning suppression.